Pengembangan Modul Cerita Rakyat Terintegrasi Latar Cerita Daerah Sulawesi Selatan pada Siswa Sekolah Dasar - Lisnawati, Lisnawati (Institut Agama Islam Negeri Palopo, 2021)
The research aims to identify needs, develop the design and level of validity of the integrated folklore learning module as a background story in the area of South Sulawesi class IV MI Datok Sulaiman. The method used by researchers is Research & Development (R & D), while in developing a product in the form of teaching materials the researcher refers to the 4D model which consists of three stages, namely: the define stage, the design stage, and the developing stage. This research was conducted at MI Datok Sulaiman which is located at JL. Dr. Ratulangi NO, 16 Balandai, Bara District, Palopo City. The instruments used by researchers were questionnaires, interviews, and tests of students' understanding. The results of the needs analysis show that students like modules that are colored, pictured, and have multiple-choice assignments. And the results of student questionnaires such as 72% liked the task of telling and writing the contents of the pictures provided by the teacher. Systematically, the integration starts from folklore material into two main sub-materials, namely: intrinsic elements and the main character of a story. The decomposition of the material becomes a component of the folklore that has been written in the module. The results of the validity of teaching materials were assessed by three experts, including content experts, design experts, and pre-activation. The validity range was 0.78-1.00 and was included in the valid and very valid category.